Sistema de monitoreo y adquisición de datos de parámetros eléctricos para determinar la eficiencia energética en la cámara de transformación Nº1 en las diferentes jornadas académicas de la Universidad Técnica de Cotopaxi, Campus Matriz, periodo 2020. - Lasluisa Canchignia, Rodrigo Patricio (2020)
This technological proposal refers to the implementation of a monitoring and data acquisition system in the general board of Block B and Block A installed in the transformation chamber No. 1, where the purpose of its development is focused on the use of communication protocols between devices, so that it could be possible to register the data that is being generated through the automation of the monitoring system which is made up of a Pac3220 Meter that is linked to the Siemens Simatic IoT2040 gateway, in such a way that a process is generated, where the data is read, processed and sent automatically to the cloud, this action is based on a process computer / server, considering that communication protocols and internet connection are the basis of Industry 4.0 or the Internet of Things (IoT). Within the main characteristics offered by this system, the possibility to supervise through the remote monitoring the energy consumption conditions that is taking place in the different academic sessions of the Cotopaxi Technical University, in the same way there is internet connectivity, which allows the capacity to collect and record data to be developed more efficiently on the measurements taken by the equipment and their respective fluctuations based on the operation of the facilities.